Konsep Pendidikan Humanis Perspektif Islam dan Aplikasinya dalam Proses Belajar Mengajar Menurut al-Zarnuji - admin, Ahmad Khumaidi; Siti Maryam (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2021)
Education is an effort to learn with the help of others to achieve its goals. The purpose of humanist education or learning / gaining knowledge here is a certain condition that is used as a reference to determine the success of learning / education. In other words, the purpose of education / learning in the sense of micro education is the desired condition after individuals carry out learning activities. Goals are what humans proclaimed, put as the center of attention, and for the sake of realizing it he organizes his behavior. The goal is very important because it serves as the end of all activities, directing all educational activities. From this, this study aims to explore the basic concepts of humanist education in the Islamic perspective according to al-Zarnuji and the Islamic perspective on human education (humanization) as education that seeks to humanize humans, and its application in the teaching and learning process. To achieve the above objectives, there are several approaches used by the author, namely the method of discussion which includes deductive methods, inductive methods, comparative methods, and descriptive methods. while the second uses library research, namely by collecting information from reading materials, books, magazines, seminars and other sources that are relevant to the subject matter, after that it is studied and researched carefully and then the data is generalized and sorted. -sorted based on suitability with the theme of the study, then the data obtained from the results of the sorting, analyzed in depth with the Islamic analysis method (content analysis) Keywords: Humanist education, its application in the teaching and learning process.